Criminal Law Aspects of International Child Abduction - Batrićević, Ana; Paunović, Nikola (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
As a complex and expanding global problem, international child abduction causes many legal consequences. Although the Convention on the Civil Aspects of International Child abduction, adopted in 1980, sets the grounds for cooperation of relevant state authorities in order to provide prompt return of the abducted child to the state of his or her habitual residence and protect his or her best interests, numerous other issues such as criminal liability of parents, protection of child's rights and protection of right to family life, arise therein. The authors of this paper highlight different etiological and legal aspects of international child abduction and discuss the link between this phenomenon and other similar offences, such as abduction, human trafficking, trafficking in minors for adoption and domestic violence, with special focus on Serbian legislation. The authors also point out the most disputable issues regarding international child abduction in the practice of the European Court of Human Rights and key dilemmas in the practical implementation of national and international frameworks for its prevention.